Osadnictwo łużyckich pól popielnicowych w dorzeczu Orlicy - Bláhová, Zuzanna; Beková, Martina
The paper presents the recent state of knowledge and new findings from the Urnfield Period (Reinecke BC/BD – HD/LtA) on the territory of the district of Rychnov nad Kněžnou. The landscape and natural conditions, the development of source basis and site types form the Bronze and Early Iron Age are described. The aim of future analysis will be to solve questions concerning the settlement development and the engagement of this region to the communication net at that time, focusing possible contacts to the neighbouring region of Kladsko/Kłodzko.
Keywords: Lusatian culture; settlement; Eastern Bohemia; Urnfield period; Orlica river